Tax Revenue Diversification in Indonesia - Martiyus, Jefrio (Jurnal Ekonomi & Studi Pembangunan, 2021)
State finances are a vital issue that is still being debated among scholars. This paper focuses on revenue diversification issues affecting the variables in this study, discussed by Deborah A Carrol in the USA. Some researchers believe that revenue diversification is an alternative path to stabilize state accounts in a crisis. Furthermore, diversification can also capture policy reactions to political and economic constraints. Using panel data analysis, it was found that four significant variables affected the tax revenue diversification, including average monthly salaries, per capita expenditure, homeownership, and the Gini Ratio. This study uncovered that Indonesia's tax revenue sources were not diverse, with more than 47 percent coming from income taxes. In theory, this condition should get more attention from the government because the more diverse the revenue, the more stable the government account becomes.